The Post-operaist Approach to the Formal and Real Subsumption of Labor Under Capital. Seminar with Michael Hardt. - Hardt, Michael (Praktyka Teoretyczna, 2015)
The Post-operaist Approach to the Formal and Real Subsumption of Labor Under Capital. Seminar with Michael Hardt.